2021
DOI: 10.1037/cou0000544
|View full text |Cite
|
Sign up to set email alerts
|

Depression and mentalizing: A psychodynamic therapy process study.

Abstract: The present study aimed to explore the relationship between changes in depressive symptoms and the capacity to mentalize over the course of a 3-month inpatient psychodynamic therapy in a sample of 56 patients with depression. Depressive symptoms and mentalizing were assessed weekly during treatment and at 1-year follow-up with the Beck Depression Inventory and the Reflective Functioning Questionnaire (RFQ). Data were analyzed using Latent Growth Curve (LGC) modeling with structured residuals. In the total samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…As previously described, Halstensen et al (2021) found a complex pattern of change in BDI-II with improved fit for a nonlinear change model including the quadratic function for depressive symptoms over the 12-week treatment period (baseline: M = 15.34, SD = 7.61; linear change during treatment: M = 1.01, p = .005; SD = 1.97, p = .010; quadratic change during treatment: M = −0.08, p < .001; SD = 0.13, p = .021; posttreatment to follow-up: M = −0.07, p = .016; SD = 0.13, p = .005). The model first showed a nonlinear increase in symptoms and then a reduction until the posttreatment time, with a lower level than that at baseline.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As previously described, Halstensen et al (2021) found a complex pattern of change in BDI-II with improved fit for a nonlinear change model including the quadratic function for depressive symptoms over the 12-week treatment period (baseline: M = 15.34, SD = 7.61; linear change during treatment: M = 1.01, p = .005; SD = 1.97, p = .010; quadratic change during treatment: M = −0.08, p < .001; SD = 0.13, p = .021; posttreatment to follow-up: M = −0.07, p = .016; SD = 0.13, p = .005). The model first showed a nonlinear increase in symptoms and then a reduction until the posttreatment time, with a lower level than that at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Some individual variation around this mean change was found, indicating that some patients experienced stronger reductions than others. See Halstensen et al (2021), for further analysis of the reduction in depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Es una capacidad transdiagnóstica, transteórica y dinámica, que favorece la regulación emocional, la empatía (Bilbao Bilbao, 2021), la resiliencia, la reducción del estrés, y la interpretación de las situaciones (Fonagy et al, 2002). Se ha evidenciado la eficacia de las intervenciones en mentalización en la disminución de problemas de salud mental (Luyten et al, 2020;Halstensen et al, 2021;Bo et al, 2017;Jørgensen et al, 2013). Dado que un modo reflexivo de funcionamiento puede adaptarse mejor a los entornos dominados por la incertidumbre (Carver et al, 2017), y entendiendo que una alta mentalización contribuye a la consolidación de dichos modos, se podrían sugerir, con el objetivo de fortalecer la protección de la salud mental para esta y futuras crisis, la implementación de intervenciones que aumenten y fomenten la capacidad de mentalizar de las personas.…”
Section: Introductionunclassified